Analysis Of The Communication Policy Of The North Sumatra Provincial Government In Increasing Regional Original Revenue (Pad) In The Motor Vehicle Tax Sector - Achmad Fadly; Syukur Kholil; Anang Anas Azhar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This paper focuses on direct observation and in-depth analysis to explore various aspects of communication policies used by the North Sumatra Provincial Government to increase Regional Original Revenue (PAD). This study uses a qualitative descriptive approach. This research occurred at the North Sumatra Provincial Government Headquarters on Jalan Diponegoro No. 30, Madras Hulu, Medan Polonia District, Medan City, North Sumatra. This research lasted for a duration of three months, starting from February 2024 to April 2024. Data sources refer to sources where research data is obtained directly or indirectly. The data collection uses non-participatory observation, semi-structured interviews, and documentation studies; through triangulation techniques, researchers can confirm the correctness of the findings by comparing and verifying various data sources. The results of the study show that the communication strategy of the North Sumatra Provincial Government to increase public understanding of the importance of paying Motor Vehicle Tax (PKB) is carried out through an integrative and inclusive approach. Second, the friendly and professional service at Samsat’s offices creates a positive experience that encourages taxpayer compliance. Third, the community is invited to dialogue through participatory education in schools, villages, and public forums to understand the importance of PAD’s contribution. Fourth, collaboration between agencies ensures consistent message delivery and educational law enforcement so that the public is more motivated to obey without feeling intimidated. Meanwhile, the Islamic communication approach applied by the North Sumatra Provincial Government in increasing awareness of paying Motor Vehicle Tax (PKB) refers to the principles of Qaulan Sadiidan (right words), Qaulan Layyinan (gentle words), Qaulan Ma’rufan (good words), and Qaulan Balighan (adequate words). The obstacles faced by the North Sumatra Provincial Government (North et al. Government) in informing the Motor Vehicle Tax (PKB) policy to the public include aspects of transparency, technology, geography, communication, tax education, coordination between agencies, law enforcement and communication disruptions due to language barriers and technological infrastructure.